1999
DOI: 10.1002/(sici)1097-010x(19991001)284:5<586::aid-jez14>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Plasma steroid hormone profiles and reproductive biology of the epaulette shark,Hemiscyllium ocellatum

Abstract: Examination of the reproductive biology of the oviparous epaulette shark, Hemiscyllium ocellatum, was conducted on a wild population. Male sharks were found to reach maturity at between 55–60 cm total length (TL) and female sharks mature around 55 cm TL. Blood samples collected from mature male and female sharks were analyzed for sex steroid hormones to examine seasonal hormone patterns. Plasma samples were analyzed via radioimmunoassay techniques with female samples measured for estradiol, progesterone, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 18 publications
3
37
0
Order By: Relevance
“…Males with calcified claspers ≥120 mm long with a testes mass of ≥1·5 g and testes width of ≥7 mm were considered reproductively capable of fertilizing an ovulated follicle. These criteria are consistent with previous studies that reported similar characteristics for other mature elasmobranch species (Koob et al , 1986; Heupel et al , 1999; Conrath & Musick, 2002; Sulikowski et al , 2004) and for those used by Driggers et al (2004 a ) for blacknose sharks in the western North Atlantic Ocean.…”
Section: Methodssupporting
confidence: 91%
“…Males with calcified claspers ≥120 mm long with a testes mass of ≥1·5 g and testes width of ≥7 mm were considered reproductively capable of fertilizing an ovulated follicle. These criteria are consistent with previous studies that reported similar characteristics for other mature elasmobranch species (Koob et al , 1986; Heupel et al , 1999; Conrath & Musick, 2002; Sulikowski et al , 2004) and for those used by Driggers et al (2004 a ) for blacknose sharks in the western North Atlantic Ocean.…”
Section: Methodssupporting
confidence: 91%
“…Although the draughtboard shark was not found to have a defined seasonal reproductive pattern, variations in hormone levels followed similar trends in reproductive activity obtained from macroscopic examination of the gonads (Awruch 2007). In seasonally reproducing species such as the epaulette shark Hemiscyllium ocellatum (Heupel et al 1999), clearnose skate Raja eglanteria (Rasmussen et al 1999) and Atlantic stingray Dasyatis sabina (Tricas et al 2000), strong correlations between plasma steroid hormone levels and season have been reported. Thus, the application of this technique to seasonally reproducing species may also provide the ability to determine the timing of reproductive events such as follicle development, ovulation and gestation period.…”
Section: Discussionmentioning
confidence: 87%
“…While an association between abiotic factors and hormone levels has been demonstrated in at least three elasmobranchs ( Hemiscyllium ocellatum : [63]; Urobatis halleri : [64], [65]; Scyliorhinus canicula : [61], controlled experiments demonstrating such dependence has only been shown in male U. halleri [64], in which temperature has a role in elevating T levels.…”
Section: Discussionmentioning
confidence: 99%